2012
DOI: 10.3892/etm.2012.809
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glucocorticoid receptor gene polymorphisms on asthma phenotypes

Abstract: The clinical presentation of asthma results from complex gene-gene and gene-environment interactions. The natural variability of the DNA sequence within the NR3C1 gene affects the activity of glucocorticoid receptors (GCRs). The NR3C1 gene is localized on chromosome 5q31–q32. The gene coding for the GCR comprises nine exons. The structural domains of the GCR determine the biological functions of the functional domains. The observed resistance to glucocorticosteroids and the normal metabolic profile of Tth111I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(72 citation statements)
references
References 37 publications
1
69
0
2
Order By: Relevance
“…Asthmatic [9,10,11,19,20,21,22,40]. The patients who had been diagnosed with chronic obstructive pulmonary disease, cardiac failure of III and IV class according to the NYHA Functional Classification, renal failure, liver insufficiency, thyroid diseases, diabetes, autoimmune diseases, neoplastic diseases, unstable angina pectoris and other severe systemic diseases, were excluded from the study.…”
Section: Variablementioning
confidence: 99%
See 2 more Smart Citations
“…Asthmatic [9,10,11,19,20,21,22,40]. The patients who had been diagnosed with chronic obstructive pulmonary disease, cardiac failure of III and IV class according to the NYHA Functional Classification, renal failure, liver insufficiency, thyroid diseases, diabetes, autoimmune diseases, neoplastic diseases, unstable angina pectoris and other severe systemic diseases, were excluded from the study.…”
Section: Variablementioning
confidence: 99%
“…The control group consisted only of healthy subjects who met all the required criteria: negative results of skin prick tests for common allergens, lack of first degree relatives with asthma, allergy or atopy, lack of therapy with rifampicin, phenobarbital, phenytoin or ephedrine, lack of a physical examination and anamnesis confirming the occurrence of asthma, other pulmonary diseases, allergy, atopy and hypersensitivity to non-steroidal anti-inflammatory drugs and lack of a spirometric test confirming obturation [9,10,11,19,20,21,22,40].…”
Section: Variablementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies (van Rossum and Lamberts, 2004;De Iudicibus et al, 2011;Panek et al, 2013a) reported an association between the Tth111I SNP and increased cortisol level in the blood; additionally, these studies reported a decrease in the cortisol secretion following the administration of 1 mg dexamethasone (DEX). Additionally, carriers of the Tth111I SNP who also express the ER22/23EK SNP have been shown to induce resistance to GCs and show a normal metabolic profile Nicolaides et al, 2010;Panek et al, 2012a).…”
Section: Discussionmentioning
confidence: 99%
“…Tth111I is a restriction fragment length polymorphism (RFLP) that is coupled with the ER22/23EK SNP (rs6189 and rs6190) (Detera-Wadleigh et al, 1991;Rosmond et al, 2000;DeRijk and de Kloet, 2008;Nicolaides et al, 2010;Panek et al, 2013a). The C/G SNP in BclI (rs41423247) is associated with increased cortisol suppression (van Rossum et al, 2003;Stevens et al, 2004), while ER22/23EK (rs6189 and rs6190) (Koper et al, 1997) is believed to be associated with decreased GR sensitivity (van Rossum et al, 2002.…”
Section: Introductionmentioning
confidence: 99%